The Association between body mass index(BMI)with some pituitary gland hormones in infertile women with and without hypothyroidism in Basra Governorate - Ali S. Al-khafaji,; Abdulkareem M. Jewad, (University of Thi-Qar Journal of Science, 2023)
Obesity and being overweight are rising and becoming a global issue. Obesity has a negative impact on all body systems, including the endocrine system. The present study aimed to determine whether there is an association between BMI and pituitary gland hormones in infertile women's serum in Basra City, Iraq. The study was conducted at Ibn-Gzouan Hospital for Obstetrics and Gynecology in Basra City, southern Iraq, between October 2021 and March 2022. Thestudy included 60 infertile women (30 with hypothyroidism and 30 without hypothyroidism) aged between 18 and 45 years,with a pathological period of infertility from 2 to 15 years. The studied infertile women were divided into two groups according to the measured BMI. The first group had a BMI of less than 25 (24 women) and the second had a BMI of greater than 25 (36 women).The results showed that there are significant elevations in LH level and cortisol levels as well as in LH/FSH ratio. Cortisol showed a positive correlation with BMI (r = 0.374, p = 0.025), FSH showed a positive correlation with LH level (r = 0.428, p = 0.009) in the same direction LH showed a positive correlation win LH/FSH ratio (r = 0.668, p = 0.000). In infertile women with a BMI greater than 25, FSH showed a negative correlation with the LH/FSH ratio (r = -0.342, p = 0.041). From the above results, we can conclude that BMI is an essential parameter in any treatment of women